If you're not confused, you're not paying attention: Ochrobactrum is not Brucella - Moreno, E.; Middlebrook, E.A.; Altamirano-Silva, P.; Al Dahouk, S.; Araj, G.F.; Arce-Gorvel, V.; Arenas Gamboa, Á.; Barquero-Calvo, E.; Battelli, G.; Bertu, W.J.; Blasco, J.M.; Bosilkovski, M.; et al. (American Society for Microbiology, 2023)
Bacteria of the genus Brucella are facultative intracellular parasites that cause brucellosis, a severe animal and human disease. Recently, a group of taxonomists merged the brucellae with the primarily free-living, phylogenetically related Ochrobactrum spp. in the genus Brucella. This change, founded only on global genomic analysis and the fortuitous isolation of some opportunistic Ochrobactrum spp. from medically compromised patients, has been automatically included in culture collections and databases. We argue that clinical and environmental microbiologists should not accept this nomenclature, and we advise against its use because (i) it was presented without in-depth phylogenetic analyses and did not consider alternative taxonomic solutions; (ii) it was launched without the input of experts in brucellosis or Ochrobactrum; (iii) it applies a non-consensus genus concept that disregards taxonomically relevant differences in structure, physiology, population structure, core-pangenome assemblies, genome structure, genomic traits, clinical features, treatment, prevention, diagnosis, genus description rules, and, above all, pathogenicity; and (iv) placing these two bacterial groups in the same genus creates risks for veterinarians, medical doctors, clinical laboratories, health authorities, and legislators who deal with brucellosis, a disease that is particularly relevant in low- and middle-income countries. Based on all this information, we urge microbiologists, bacterial collections, genomic databases, journals, and public health boards to keep the Brucella and Ochrobactrum genera separate to avoid further bewilderment and harm.